2013
DOI: 10.3892/or.2013.2420
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and biological significance of microRNA-192 in pancreatic ductal adenocarcinoma

Abstract: Abstract. Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal types of human cancer. In the present study, we evaluated serum as a potential biomarker in patients with PDAC and investigated its biological functions in this disease. miRNA expression profiling of human PDACs and adjacent normal pancreatic tissues identified 16 upregulated miRNAs including miR-192 and 8 downregulated miRNAs. Quantitative real-time polymerase chain reaction (PCR) revealed elevation of serum miR-192 levels in PDAC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 32 publications
(44 reference statements)
0
75
1
1
Order By: Relevance
“…miR-192 expression was found to be downregulated significantly enough to serve as an accurate diagnostic marker of PDAC and CP, in contrast to a recent report (24). Its abnormal expression in PDAC and CP was mediated by DNA methylation at the same genomic locus within the promoter region, which showed a significant inverse correlation with the miR-192 expression in individual patients of the cohort.…”
Section: Discussioncontrasting
confidence: 88%
“…miR-192 expression was found to be downregulated significantly enough to serve as an accurate diagnostic marker of PDAC and CP, in contrast to a recent report (24). Its abnormal expression in PDAC and CP was mediated by DNA methylation at the same genomic locus within the promoter region, which showed a significant inverse correlation with the miR-192 expression in individual patients of the cohort.…”
Section: Discussioncontrasting
confidence: 88%
“…The abnormal expression of miRNAs in PDAC was previously reported (24)(25)(26); however, few studies have investigated the role of specific miRNAs in carcinogenesis and progression of PDAC. The present study has presented the first data characterizing the expression, biological functions and molecular mechanisms underlying miR-216b in PDAC.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies found that miR-192 is significantly increased in many types of cancer (39)(40)(41), but decreased in many others (42,43). Studies have also shown that p53-mediated upregulation of miR-192 prevents EMT in hepatocellular carcinoma through repression of the transcription factor ZEB2 (44).…”
Section: Discussionmentioning
confidence: 98%